The Influence of Income, Company Reputation, and Waiting Lists for Hajj on The Interest of Generation Z in Saving for Hajj Deposits in Islamic Banks. - Misbakhul Munir; Saibil, Defi Insani; Dery Alfian Saputra (Journal of Business Management and Islamic Banking, 2024)
Research Aims: The study aims to explore the influence of income, company reputation, and waiting lists for hajj on the interest of Generation Z in saving for hajj deposits in Islamic banks. Methodology: This research employs a quantitative descriptive methodology, using regression analysis tools and the SPSS 24 software. A total of 128 respondents from Cirebon Regency were surveyed to gather relevant data. Research Findings: The findings reveal that each independent variable, including income, company reputation, and waiting lists, significantly influences the dependent variable, with the highest impact attributed to company reputation. This demonstrates that a positive image of the bank plays a crucial role in attracting potential customers. Theoretical Contribution: This study contributes to the existing literature by highlighting the key factors influencing Generation Z's motivation to save for hajj in Islamic banks, specifically emphasizing the importance of company reputation in this context. Research limitation and implication: The study is limited to the Cirebon Regency and may not be generalizable to other regions. Future research could expand the demographic scope and examine additional factors that influence saving behaviors among different populations. The findings imply that banks should strive to maintain a positive reputation to effectively attract and retain customers, alongside considering other relevant factors in product marketing.